2022
DOI: 10.1016/j.agsy.2022.103367
|View full text |Cite
|
Sign up to set email alerts
|

Perceived effects of COVID-19 restrictions on smallholder farmers: Evidence from seven lower- and middle-income countries

Abstract: CONTEXT The COVID-19 pandemic caused unprecedented global disruption and continues to wreak havoc. Dire predictions were made about the risks to smallholder farmers in lower- and middle- income, but hard data have been lacking. We present the results from 9201 interviews with smallholder farmers from seven countries. OBJECTIVE The objectives are to describe: i) how farmers perceive the key effects of the COVID-19 pandemic and containment measures on livelihoods and food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 42 publications
3
36
0
3
Order By: Relevance
“… Hammond et al (2022) analysed a large collection of smallholder farmer surveys from seven countries in Sub-Saharan Africa and South-east Asia to assess their self-reported impacts of pandemic mitigation policies and their consequent coping strategies. They found consistent reporting from smallholders across these disparate countries on negative livelihood and food security consequences of pandemic mitigation measures like restricted movements of individuals and disruptions to agricultural markets.…”
Section: Comparative/theoretical Piecesmentioning
confidence: 99%
See 2 more Smart Citations
“… Hammond et al (2022) analysed a large collection of smallholder farmer surveys from seven countries in Sub-Saharan Africa and South-east Asia to assess their self-reported impacts of pandemic mitigation policies and their consequent coping strategies. They found consistent reporting from smallholders across these disparate countries on negative livelihood and food security consequences of pandemic mitigation measures like restricted movements of individuals and disruptions to agricultural markets.…”
Section: Comparative/theoretical Piecesmentioning
confidence: 99%
“… Tougeron and Hance (2021) describe potential costs to agricultural science, extension, and risk mitigation due to restricted access to agricultural operations, which may result in future costs to agriculture (e.g., reduced agricultural pest surveillance by research and extension personnel). Documenting these experiences can hopefully lead to improved pandemic mitigation strategies that are able to both manage public health risks as well as the costs of human movement restrictions ( Hammond et al, 2022 ).…”
Section: Emergent Themes From the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Мировая проекция экономических проблем (результаты исследований функционирования малых ферм в Китае, странах Азии, Африки), вызванных пандемическим воздействием, состояла практически из идентичных трендов, которые заключались в многоуровневых ограничениях мобильности, экономическом спаде производства, переформатировании каналов сбыта произведенной сельскохозяйственной продукции. У малых товарных домохозяйств в данных регионах средняя доля экономических потерь составила около 50 % [13].…”
Section: параметры экономических изменений функционирования малых кфх...unclassified
“…Household sample surveys have been used in different aspects related to the COVID-19 pandemic. A review in PUBMED as of May 18, 2022, identified publications on the following aspects: impact on food security (3), effect on household health expenditure (4), data collection (5), effects of control restrictions (6,7), educational effects (8), social distancing (9), effects on family well-being (10)(11)(12), relationship with smoking (13), prevalence (14)(15)(16)(17). In the specific topic of vaccines, only one publication was identified in which the use of household surveys to explore the acceptance of vaccines against COVID-19 was reported (18).…”
Section: Introductionmentioning
confidence: 99%